Analysis of actual results of drug supply implementation within framework of High-Cost Nosologies Program - O. I. Ivakhnenko; V. V. Ryazhenov; E. A. Maksimkina; V. S. Fisenko; O. V. Savoskin; M. M. Kuznetsova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2024)
The accessibility and pharmaceutical care coverage are linked to political, economic and managerial decisions. That fact necessitates the evaluation of the state programs results in the field of the drug provision.The aim of the work was to assess the quantitative results of the implementation of the High-Cost Nosologies program in the Russian Federation from 2008 to 2023 to determine further vectors of its improvement.Materials and methods. The regulatory base of the work was made up of the Russian Federation legislation in the field of the drug provision. The open sources were used as the research information base for the data collection and analysis: reports of federal and regional executive authorities, materials of specialized conferences, results of published studies.Results. The drug coverage under the High-Cost Nosologies (VZN) program is provided for 14 nosologies, 11 of which are classified as orphan diseases. Since its implementation, the HCNs program has been expanded twice by including new nosologies in 2019 and 2020. As of 01 October 2023, the number of patients in the Federal Register of VZN was 263 721 people, which was 13.58 times greater compared to 2008. The drug provision is carried out according to the list of 47 INNs. The amount of funding for the program increased from RUB 32 bn in 2008 to RUB 87.96 bn in 2023. The most resource-intensive nosologies include hemophilia, multiple sclerosis and oncohematology.Conclusion. The main quantitative characteristics of the implementation of the HCNs program and the identified vectors for its further improvement have been analyzed in this study. The results obtained can be used to conduct analytical studies, including the ones within nosologies and nosological groups included in the program, in order to optimize a pharmaceutical care. The focus of improving the implementation of the VZN program is related to the improvement of the legal framework, a patient treatment paradigm and approaches to its financing.